Local recurrence after local excision of early rectal cancer: a meta‐analysis of completion TME, adjuvant (chemo)radiation, or no additional treatment. Issue 13 (16th September 2020) - van Oostendorp, S. E.; Smits, L. J. H.; Vroom, Y.; Detering, R.; Heymans, M. W.; Moons, L. M. G.; Tanis, P. J.; de Graaf, E. J. R.; Cunningham, C.; Denost, Q.; Kusters, M.; Tuynman, J. B.
Abstract : Background: The risks of local recurrence and treatment‐related morbidity need to be balanced after local excision of early rectal cancer. The aim of this meta‐analysis was to determine oncological outcomes after local excision of pT1–2 rectal cancer followed by no additional treatment (NAT), completion total mesorectal excision (cTME) or adjuvant (chemo)radiotherapy (aCRT). Methods: A systematic search was conducted in PubMed, Embase and the Cochrane Library. The primary outcome was local recurrence. Statistical analysis included calculation of the weighted average of proportions. Results: Some 73 studies comprising 4674 patients were included in the analysis. Sixty‐two evaluated NAT, 13 cTME and 28 aCRT. The local recurrence rate for NAT among low‐risk pT1 tumours was 6·7 (95 per cent c.i. 4·8 to 9·3) per cent. There were no local recurrences of low‐risk pT1 tumours after cTME or aCRT. The local recurrence rate for high‐risk pT1 tumours was 13·6 (8·0 to 22·0) per cent for local excision only, 4·1 (1·7 to 9·4) per cent for cTME and 3·9 (2·0 to 7·5) per cent for aCRT. Local recurrence rates for pT2 tumours were 28·9 (22·3 to 36·4) per cent with NAT, 4 (1 to 13) per cent after cTME and 14·7 (11·2 to 19·0) per cent after aCRT. Conclusion: There is a substantial risk of local recurrence in patients who receive no additional treatment after local excision, especially those with high‐risk pT1 and pT2 rectal cancer. The lowest recurrence risk is provided by cTME; aCRT has outcomes comparable to those of cTME for high‐risk pT1 tumours, but shows a higher risk for pT2 tumours. Abstract : This meta‐analysis showed that patients who undergo no additional treatment after local excision of pT1–2 rectal cancer have a high risk of local recurrence, especially those with high‐risk pT1 and pT2 lesions. The risk of local recurrence after adjuvant (chemo)radiotherapy for high‐risk pT1 tumours seems to be similar to that after completion TME. For pT2 tumours, adjuvant (chemo)radiotherapy seems less effective than radical surgery. No additional therapy after local excision of pT1‐2 associated with high risk of local recurrence Abstract : Antecedentes: Tras una resección temprana de un cáncer de recto localizado, hay que considerar el equilibrio entre el riesgo de recidiva local y la morbilidad relacionada con el tratamiento. El objetivo de este metaanálisis era determinar los resultados oncológicos tras la resección de un cáncer de recto pT1‐T2 seguida de ningún tratamiento adicional ( no additional treatment, NAT), escisión total del mesorrecto ( completion total mesorectal excision, cTME) o quimiorradioterapia adyuvante ( adjuvant chemoradiotherapy, aCRT). Methods: Se llevó a cabo una búsqueda sistemática en PubMed, Embase y biblioteca Cochrane. La variable principal de resultado era la recidiva local ( local recurrence, LR). En el análisis estadístico se calcularon las medias ponderadas de proporciones. Resultados: Se incluyeron en el análisis 76 estudios con un total de 4.793 pacientes. NAT fue evaluada en 72 estudios, cTME en 13 y aCRT en 28. La tasa de LR para NAT en tumores pT1 de bajo riesgo era de 6, 7% (i.c. del 95% 4, 8‐9, 3). No se observaron casos de LR en tumores pT1 de bajo riesgo tras cTME o aCRT. La tasa de LR para tumores pT1 de alto riesgo fue de 13, 6% (i.c. del 95% 8, 0‐22, 0) para la resección local como único tratamiento, 4, 1% (i.c. del 95% 1, 7‐9, 4) para cTME y 3, 9% (i.c. del 95% 2, 0‐7, 5) para aCRT. La tasa de LR para tumores pT2 fue de 28, 9% (i.c. del 95% 22, 3‐36, 4) para NAT, 4, 3% (i.c. del 95% 1, 4‐12, 5) para cTME y 14, 7% (i.c. del 95% 11, 2‐19, 0) para aCRT. Conclusión: Tras la resección local de cáncer pT1 de alto riesgo y pT2, existe un riesgo sustancial de recidiva local en ausencia de tratamiento adicional. La escisión total del mesorrecto se asocia con el menor riesgo de recidiva. La quimiorradioterapia adyuvante ofrece resultados similares a la escisión total del mesorrecto en tumores pT1 de alto riesgo, pero presenta un mayor riesgo en tumores pT2.